1951
DOI: 10.1084/jem.93.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mechanism of the Shwartzman Phenomenon

Abstract: The intradermal injection of certain bacterial products in rabbits, followed after a suitable interval of time by the intravenous injection of similar material, results in an intense hemorrhagic-necrotic lesion at the site of the intradermal injection. This phenomenon, first described by Shwartzman (1), may also be produced by an intmdermal injection of a protein antigen in an appropriately sensitized rabbit, followed by an intravenous injection of bacterial products (2). Local infection with certain bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

1952
1952
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(38 citation statements)
references
References 7 publications
2
36
0
Order By: Relevance
“…Since the preformed antibodies appear to react with antigens in the transplants, clotting could be induced directly by the antibody-antigen reaction [38][39][40] or by the consequent tissue injury. In addition, antibody-antigen reactions attract polymorphonucleur leukocytes via C′ activation, 41 and these white cells appear capable of inducing clotting 42 and are an important if not essential intermediary in the causation of the thrombosis seen in the local 43 and generalized 42 Shwartzman reactions. Heavy accumulations of polymorphonuclear leukocytes and thrombosis have been seen in man, in whom preformed antibodies induced immediate hyperacute rejections of renal transplants.…”
Section: Discussionmentioning
confidence: 99%
“…Since the preformed antibodies appear to react with antigens in the transplants, clotting could be induced directly by the antibody-antigen reaction [38][39][40] or by the consequent tissue injury. In addition, antibody-antigen reactions attract polymorphonucleur leukocytes via C′ activation, 41 and these white cells appear capable of inducing clotting 42 and are an important if not essential intermediary in the causation of the thrombosis seen in the local 43 and generalized 42 Shwartzman reactions. Heavy accumulations of polymorphonuclear leukocytes and thrombosis have been seen in man, in whom preformed antibodies induced immediate hyperacute rejections of renal transplants.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Shwartzman phenomenon can be prevented by administration of nitrogen mustard, in doses that produce granulocytopenia but minimal or no thrombocytopenia (2,23).…”
Section: Discussionmentioning
confidence: 99%
“…Baltimore) PLATES 17 AND 18 (Received for publication, September 10, 1954) There are many indications that the effects of endotoxin upon blood vessels (1), leucocytes (2,3), and coagulation (4)(5) are important in production of the Shwartzman reaction. The effects of endotoxin upon blood vessels and leucocytes cannot be disputed, but involvement of platelets in the intravascular clotting of the Shwartzman phenomenon has never been established with certainty.…”
Section: (From the Department Of Medicine The Johns Hopkins Universimentioning
confidence: 99%
“…Extensive study has revealed much about the processes that underlie the Arthus reaction. The reaction is, as mentioned above, dependent on complement, and can be inhibited by decomplementation with cobra venom factor, anti-complement antibodies or by soluble complement receptors (Stetson & Good, 1951;Humphrey, 1955;Ward & Cochrane, 1965;Cochrane et al, 1970;Cochrane & Janoff, 1974;Rossi et al, 1992). We have previously demonstrated a role for platelet-activating factor Rossi et al, 1992), and for vasodilator prostaglandins in the plasma extravasation associated with the RPA reaction.…”
Section: Monoclonal Antibodiesmentioning
confidence: 92%
“…We have previously demonstrated a role for platelet-activating factor Rossi et al, 1992), and for vasodilator prostaglandins in the plasma extravasation associated with the RPA reaction. Neutrophil dependence has been demonstrated by the fact that RPA reactions are suppressed in neutrophil-depleted animals (Stetson & Good, 1951;Humphrey, 1955). …”
Section: Monoclonal Antibodiesmentioning
confidence: 99%